Arabic Learning Planning at Radio Station: Perencanaan Pembelajaran Bahasa Arab di Stasiun Radio - Imam Rohhani; Istikomah Istikomah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe how the planning of Arabic learning is implemented at Suara Al-Iman Radio Surabaya. This research is a descriptive research through qualitative approach with interview, observation and documentation methods. Collected and proven data are analyzed through three stages: (1) stages of data reduction, (2) stage of data presentation, and then (3) stages of concluding. The results of the study indicate that the Arabic learning planning at Suara Al-Iman Radio Surabaya has been carried out well by the director and teachers. Learning planning by director includes: a) Determination of the learning objectives; b) Determination of the program of events and scheduling; c) Determination of the human resources d) Determination of the curriculum. While the lesson planning carried out by Suara Al-Iman Radio teachers includes: a) Preparation of the learning materials; and b) Determination of the suitable method.